The “hermit priest” and the sacred-dominion of courage. Nietzsche and the Genealogy of Morals - Vergara Henríquez, Fernando José (Estudios de Filosofía, 2011)
The present article develops the Nietzschean diagnosis on the Moral Condition of the Western Judeo- Christian Tradition. Exploring Nietzsche´s critique in The Genealogy of Morals, we want to undertake, under the Hermeneutic Key of Sense, to show that the hermit priest rises as a figure of domination of the moral feelings that has a sacred character, turning into a sort of administrator of the Sense of Suffering, of Grief, of Guilt and of Bad Conscience.